2010
DOI: 10.1016/j.ejvs.2010.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Changing Profiles of Diagnostic and Treatment Options in Subclavian Artery Aneurysms

Abstract: The profiles of diagnostic and treatment options of SAAs are changing. Although guidelines considering timing of intervention may not be conducted from available literature, intervention appears to be indicated, especially in distal SAAs, due to the risk of thrombo-embolic complications. Endovascular repair and hybrid procedures appear to be the preferred treatment modalities, due to a lower rate of cardiopulmonary complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 94 publications
1
67
0
13
Order By: Relevance
“…Clinical presentation varies from asymptomatic mass to compression of the neighboring anatomic structures or distal embolization. Dysphagia, dyspnea, hemoptysis, and hoarseness of voice from esophageal, tracheal, lung, phrenic, and right recurrent laryngeal nerve compression have been described ( 5 ). Thoracic CTA is the preferred imaging modality since it helps for diagnosis and operational approach to subclavian artery aneurysm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical presentation varies from asymptomatic mass to compression of the neighboring anatomic structures or distal embolization. Dysphagia, dyspnea, hemoptysis, and hoarseness of voice from esophageal, tracheal, lung, phrenic, and right recurrent laryngeal nerve compression have been described ( 5 ). Thoracic CTA is the preferred imaging modality since it helps for diagnosis and operational approach to subclavian artery aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Vierhout et al ( 5 ) in a 2010 review found 394 cases of subclavian artery aneurysm in 381 patients. Half of them (51%) presented with pulsatile mass, shoulder pain, and non-specific chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…The common causes of SAAs were atherosclerosis, thoracic outlet syndrome, infection, trauma, and congenital arterial anomalies such as Marfan syndrome 1,2. In particular, proximal aneurysms were caused by atherosclerosis (19%), collagen disorder (18%), trauma (15%), infection (13%), and in-hospital procedures (12%) 2.…”
Section: Discussionmentioning
confidence: 99%
“…Although SAAs can be asymptomatic, they can also cause life-threatening complications such as rupture, thrombosis, or embolism and can result in symptoms caused by local compression 2. In a meta-analysis of 394 native SAAs, rupture occurred in 9% of patients, with an associated mortality of 19% 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation